2012
DOI: 10.1021/ja210992b
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring Molecular Chromophores to Colloidal Gold Nanocrystals: Surface-Enhanced Raman Evidence for Strong Electronic Coupling and Irreversible Structural Locking

Abstract: High-affinity anchoring groups such as isothiocyanate (-N=C=S) are often used to attach organic chromophores (reporter molecules) to colloidal gold nanocrystals for surface-enhanced Raman scattering (SERS), to atomically smooth gold surfaces for tip-enhanced Raman scattering (TERS), and also to scanning tunneling microscopy (STM) probes (nanosized electrodes) for single-molecule conductance measurements. However, it is still unclear how the attached molecules interact electronically with the underlying surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…Isothiocyanide (-N=C=S) groups are also known to possess high affinity versus gold. So far this affinity has mostly been exploited to attach organic chromophores to colloidal gold nanocrystals or to nanoscale electrodes for surface-enhanced Raman scattering (SERS) applications [23], formation of metal junctions for molecular electronic applications [24], bioimmunoassays [25] and cancer therapy applications [26]. However, recent theoretical work by Sikora et al showed that bis-isothiocyanide molecules can also be used as alternative to dithiols as conjugation molecules for bridging two or more nanocrystals together [27], whereby the lowest reactivity of isothiocyanide groups compared to thiols for citrate stabilized gold nanoparticles was shown useful to achieve good control in the growth rate of nanoparticle clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Isothiocyanide (-N=C=S) groups are also known to possess high affinity versus gold. So far this affinity has mostly been exploited to attach organic chromophores to colloidal gold nanocrystals or to nanoscale electrodes for surface-enhanced Raman scattering (SERS) applications [23], formation of metal junctions for molecular electronic applications [24], bioimmunoassays [25] and cancer therapy applications [26]. However, recent theoretical work by Sikora et al showed that bis-isothiocyanide molecules can also be used as alternative to dithiols as conjugation molecules for bridging two or more nanocrystals together [27], whereby the lowest reactivity of isothiocyanide groups compared to thiols for citrate stabilized gold nanoparticles was shown useful to achieve good control in the growth rate of nanoparticle clusters.…”
Section: Introductionmentioning
confidence: 99%
“…11 RBITC molecules can tightly adsorb and anchor around AuNP surfaces by means of the strong affinity between the ITC group and Au. 24 In general, the most commonly used 13 nm AuNPs are prepared using a citrate reduction method and are stabilized by the negatively-charged citrate. Upon addition of RBITC, the citrate, weakly adsorbed on Au surfaces, is replaced by RBITC molecules through Au–ITC bonds.…”
Section: Resultsmentioning
confidence: 99%
“…We thus expect that RhB adsorbs on both the small Au 15 spheres and the exposed Au surface of the Janus particles (1 molecule per 2 nm 2 of total Au surface available). 52 Therefore, two Raman-active species are incorporated within the final nanostructures: RhB in the hot spots generated at the gaps between assembled Au particles and 4-MBA at the gold− silica interface of the Janus nanoparticles. Importantly, addition of the dye did not trigger aggregation of the particles, as indicated by UV−vis spectroscopy (Figure 2).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%